KEY FACTORS ASSOCIATED WITH LOW BIRTH WEIGHT AT TERM IN NEPAL: A CASE CONTROL STUDY - Laxmi Shakya, Karuna; Shrestha, Naveen; Kumar Poudyal, Amod; Prasad Koju, Rajendra; Oyloe, Peter; Raj Onta, Sharad (International Journal of Clinical and Biomedical Research, 2015)
Background:Low Birth Weight (LBW) is a major public health problem in developing countries including Nepal. Nepal has a prevalence of LBW of 21%. There are various factors associated to high prevalence of LBW. This study aimed to identify specific factors associated to LBW at term in hospital settings in Nepal. Methodology: This study used a hospital based case control design. Hospital nurses interviewed mothers aged 15-45 years who had delivered a full term, single and live baby. Results: A total of 1533 respondents (511 cases and 1022 controls) were taken which is slightly more than the estimated sample size. The mean weight of newborns among case group was 2215 gm (SD:203); and among control group was 3012gm (SD:367). This study revealed that factors such as mothers under 20 years old (OR=1.436, 95% CI:1.074-1.920); height below 145cm (OR=1.504, 95% CI:1.087 -2.083); primigravida (OR=1.423, 95% CI:1.132-1.788); illiterate (OR=1.407 95% CI:1.011-1.957); <4 ANC visits (OR=1.534, 95% CI:1.202-1.957); and iron supplement <180 tabs (OR=1.434, 95% CI:1.152-1.786) were associated with LBW. However, variables like <20 years at the first pregnancy (OR=1.139, 95% CI: 0.904-1.433), disadvantaged ethnicity (OR=1.077, 95% CI: 0.861-1.347) were not associated with LBW in this study.Conclusion: Maternal height, education, number of ANC visits, and iron consumption were strong predictors for LBW in Nepal. It would benefit the country to develop effective strategies on maternal nutrition, female education, and quality ANC to overcome LBW. KEYWORDS: Low Birth Weight; Socio-demographic and antenatal care, Case control design.